2016
DOI: 10.1542/hpeds.2015-0111
|View full text |Cite
|
Sign up to set email alerts
|

Parental Understanding of Hospital Course and Discharge Plan

Abstract: Although parents were generally knowledgeable about hospital course and discharge plan, areas for improved communication were identified. Individualized counseling about hospital course and discharge plan should be initiated for all parents early during hospitalization. Methods that assess and bolster caregiver comprehension and minimize dependence on written instructions may help with transition to outpatient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…In addition to medical information, they need conversations with the right people, access to appropriate resources at the right time, and an acknowledgment from providers that their emotional experiences are valid. These findings build on recent studies indicating that parents and providers lack shared understanding (e.g., Bhansali et al, 2016; Khan et al, 2016). Developing shared understanding goes beyond simple information transmission (Hart et al, 2006; Wanzer et al, 2004).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In addition to medical information, they need conversations with the right people, access to appropriate resources at the right time, and an acknowledgment from providers that their emotional experiences are valid. These findings build on recent studies indicating that parents and providers lack shared understanding (e.g., Bhansali et al, 2016; Khan et al, 2016). Developing shared understanding goes beyond simple information transmission (Hart et al, 2006; Wanzer et al, 2004).…”
Section: Discussionsupporting
confidence: 85%
“…First, parents and providers may not have shared understanding of pediatric patients’ conditions or care (e.g., Bhansali et al, 2016; Khan et al, 2016). For example, Khan et al (2016) found that although parents and providers reported a shared understanding in the context of hospital night shifts, objective measures of shared understanding (i.e., agreement scores for reason for admission, overall plan, and overnight plan) revealed 45% of the parent–providers lacked shared understanding.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…¶ Researchers for many studies assessed knowledge of multiple subdomains of medication instructions (eg, dose, frequency, duration) as a conglomerate outcome, 49,54,61,82,83 whereas researchers for 1 study assessed whether parents were aware if a change was made to the medication regimen. 56 The percent of parents with accurate subdomain-specific knowledge varied on the basis of the study and specific subdomain: 62% to 94% knew the correct medication dose, 50 94% frequency, 50,53,65,81 24% to 87% name, 50,53,61 34% to 65% duration, 53,65 70% to 91% indication, 50,65 and 47% side effects. 53 Studies in which execution of medication instructions was assessed fell into 2 categories: medication dosing or adherence.…”
Section: Medications (28 Studies)mentioning
confidence: 99%
“…51 Variables associated with more medication errors included having multiple medications, 61,81 limited English proficiency, 75,90 older child age, 37,38,59,78 and public or no insurance. 37,81,84 Follow-up Appointments (34 Studies) Researchers for 3 studies assessed knowledge of follow-up appointment instructions, 53,56,61 with up to 64% of parents not being aware of important follow-up information. 53 Researchers for 32 studies examined rates of follow-up appointment attendance (by parental report or electronic medical record review).…”
Section: Medications (28 Studies)mentioning
confidence: 99%